UPAYA PENERAPAN BUKU CERMAT UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PESERTA DIDIK KELAS 1 SD - Rahayu, Tira; Astri Sutisnawati; Hamdani Maula, Lutfhi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The research proposal outlines and effort to improve the initial reading ability of first grade elementary school students true the application of buku cermat. The background highlight the law initial reading comprehension a most students, necessitating inovatif and contextual learning media. The study aims to describe the implementation process for buku cermat and unalisis impact on students reading ability. Employing qualitative with classroom action research a course to cycles, the metodologi involves planning observing, and reflecting. Data collection utilizes observation, interview, documentation and inisial reading tests. Preliminary finding from the proposal indicate that buku cermat has a positif and signifikan effect with the average reading score increasing from allow of 50 in pr cycles to 80 in Cycles II, demonstrating improve recognition of letters and syllables. The expected out count is a signifikan and chainsment in students initial reading skill motivation and confidence.